Are Binary Copper Sulfides/Selenides Really New and Promising Thermoelectric Materials?. Issue 9 (12th February 2014) - Dennler, Gilles; Chmielowski, Radoslaw; Jacob, Stéphane; Capet, Frédéric; Roussel, Pascal; Zastrow, Sebastian; Nielsch, Kornelius; Opahle, Ingo; Madsen, Georg K. H.
<x xml:space="preserve">Abstract</x> Copper sulfides and copper selenides have recently been reported as new and promising low‐cost and environmentally friendly thermoelectric materials. Here, it is shown that these materials have actually been studied for more than 190 years and the absence of commercial thermoelectric modules based on them stems from some major intrinsic issues related to these chalcogenides. Further development of these semiconductors will require addressing and solving these problems before large scale utilization can be considered.